Regional Interrelationships: A Leadership Opportunity for Health Care. Issue 1 (January 2016) - Rotarius, Timothy; Liberman, Aaron
Abstract : Given the impact that the health care industry has on the national economy, health care executives need to move beyond simply providing health care treatments and instead focus on strategically leading their regions, including the other key industry contributors in their specific regions. Geographic and economic regions can be viewed as concentric circles of influence, with each circle recognizing the resources and contributions that are specific to a region. An acknowledgement by health care executives of the regional interrelationships that exist in a specific region is necessary for health care managers to strategically lead regional interrelationships. A template for implementation of this process is included. To understand the various factors that exist within circles of influence, several distinct yet interrelated vertical bases of knowledge will be discussed. The 5 bases of knowledge examined here include the following: Health Care, Tourism, Defense and Technology, Education, and Retail. It is important to note that the resources identified in the Tourism, Defense and Technology, Education, and Retail knowledge bases all have a direct influential relationship upon the health care resources of the region. For description purposes, the Central Florida geographic and economic region will be examined for interrelationships between the 5 knowledge bases.